(untitled) (CIPEEX, 2025)
Introduction: Obesity is a chronic disease that directly compromises individuals’ quality of life. Nursing management plays an essential role in the prevention and control of excess weight. Appropriate monitoring has been shown to improve clinical outcomes and promote health. Objective: To review the scientific literature on the relevance of nursing management in obesity. Methods: This literature review was conducted using the PICO strategy. The following articles in Portuguese, published in the last five years, were included in the study: A comprehensive search was conducted in August 2025 in the PubMed, BVS, and SciELO databases. The search terms "Nursing," "Control," "Prevention," and "Obesity" were combined using the Boolean operators AND and OR. Results: The articles emphasize cardiovascular diseases, including arterial hypertension, as consequences of obesity, reinforcing the importance of nursing management in the prevention and control of these conditions. They highlight the challenges posed by factors such as inadequate treatment adherence and complications arising from untreated conditions, reinforcing the fundamental role of nursing in promoting healthy habits. Conclusion: Obesity has been shown to be strongly associated with cardiovascular disease and requires ongoing nursing care. Appropriate management strategies emphasize disease prevention and control. Despite the challenges faced, nursing plays an indispensable role in promoting healthy habits and improving quality of life.